2016
DOI: 10.1016/j.hermed.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and synergy in herbal medicine

Abstract: Antimicrobial resistance (AMR) is a serious and growing threat to human health. The development of new antibiotics is limited and slow. The tradition of synergy in herbal medicine is being used as a source of research ideas. A literature review of antimicrobial research and plant synergy published in a five year period was carried out using online databases. The in vitro findings were that most of the research reported synergy both within plants and between plants and antibiotics.Whole plant extracts and combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 23 publications
0
33
0
1
Order By: Relevance
“…Originally, an antibiotic refers to an organic compound produced by a microorganism but has the potential to destroy another microorganism although presently the term also include those produced synthetically [4]. Antibiotics resistance has occurred when a microorganism is not affected by the antibiotics used against it [5].This results majorly from the indiscriminate use of antibiotics and is a primary threat to the success of modern health care [6] and has led to the studying of medicinal plants as a conceivable means of alternative therapy [7]. For many centuries, medicinal plants have been used as medicines in the treatment of many infections and diseases either as whole plants or plant extracts [8] because of bioactive compounds present in them which offers protection against microorganisms and insects.…”
Section: Introductionmentioning
confidence: 99%
“…Originally, an antibiotic refers to an organic compound produced by a microorganism but has the potential to destroy another microorganism although presently the term also include those produced synthetically [4]. Antibiotics resistance has occurred when a microorganism is not affected by the antibiotics used against it [5].This results majorly from the indiscriminate use of antibiotics and is a primary threat to the success of modern health care [6] and has led to the studying of medicinal plants as a conceivable means of alternative therapy [7]. For many centuries, medicinal plants have been used as medicines in the treatment of many infections and diseases either as whole plants or plant extracts [8] because of bioactive compounds present in them which offers protection against microorganisms and insects.…”
Section: Introductionmentioning
confidence: 99%
“…Each phytochemical compound demonstrating a high level of bactericidal activity has the potential to stimulate the development of microbial drug resistance, as assumed above. However, a crude extract consists of multiple components, each of them being able to act at different sites of the microbial cell thereby contributing to the overall activity of the extract [92,155]. In fact, it has been repeatedly demonstrated that the process of isolation of some phytochemicals often leads to a loss or reduction in their activity.…”
Section: Safety In Numbers: Synergism In "Metabolite-metabolite" or "mentioning
confidence: 99%
“…Despite numerous studies examining the antibacterial effects of combined natural compounds such as essential oils (Palaniappan & Holley, 2010;Patrone, Campana, Vittoria, & Baffone, 2010;Periago & Moezelaar, 2001;Rivera Calo, Crandall, O'Bryan, & Ricke, 2014) or phenols and organic acids (Del Valle et al, 2016;Vasconcelos de Oliveira, Montenegro Stamford, Gomes Neto, & Leite de Souza, 2010), information on the interaction of individual phenolic compounds with resveratrol are rather scarce (Chan, 2002;Del Valle et al, 2016). In this study, the antibacterial activity of selected phenolic compounds with resveratrol was tested by the microdilution method, and their interaction as binary phenolic mixtures was described by the fractional inhibitory concentration index (FICI) (Mundy, Pendry, & Rahman, 2016;Palaniappan & Holley, 2010;Petersen, Labthavikul, Jones, & Bradford, 2006). The data presented in Table 2 indicate that mixing phenolic acids with resveratrol at an equimolar ratio generally improved their antibacterial activity.…”
Section: Antibacterial Activity Of Binary Phenolic Mixturesmentioning
confidence: 99%